"Follow the Flag" : A History of the Wabash Railroad Company - Grant, H. Roger, 1943- (Book collections on Project MUSE., 2020)
'Follow the Flag' offers an authoritative history of the Wabash Railroad Company, a once vital interregional carrier. The corporate saga of the Wabash involved the efforts of strong-willed and creative leaders, but this text provides more than traditional business history. Noted transportation historian H. Roger Grant captures the human side of the Wabash, ranging from the medical doctors who created an effective hospital department to the worker-sponsored social events.